Extraorbital sebaceous carcinoma with rapidly developing visceral metastases - CEYHAN, BERRİN (LIPPINCOTT WILLIAMS & WILKINS, 2003)
BACKGROUND. Extraorbital sebaceous carcinoma (SC) is a rare carcinoma of the skin but is known to have a good prognosis in terms of metastasis and survival. OBJECTIVE. To discuss and emphasize through the clinical and histopathologic findings and the aggressive potential of extraorbital SC and to review the corresponding literature. METHODS. We present an unusual form of extraorbital SC that has followed an aggressive course and that has metastasized rapidly. RESULTS. Local excision of the primary cutaneous tumor with negative margins did not prevent the rapid and fatal internal organ metastases. The patient did not benefit from the docetaxel chemotherapy regimen applied after the distant metastases were developed. CONCLUSION. Extraorbital SC may show a poor prognosis. Both the dermatologic surgeon and the dermatologist should be cautious of the risk of local recurrence and distant metastasis when dealing with extraorbital SC.
Keywords: SKIN; MUCOSA